2020
DOI: 10.1002/emp2.12220
|View full text |Cite
|
Sign up to set email alerts
|

The impact of public health interventions on critical illness in the pediatric emergency department during the SARS‐CoV‐2 pandemic

Abstract: Study objective The impact of public health interventions during the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) pandemic on critical illness in children has not been studied. We seek to determine the impact of SARS‐CoV‐2 related public health interventions on emergency healthcare utilization and frequency of critical illness in children. Methods This was an interrupted time series analysis conducted at a single tertiary pediatric emergency department (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 33 publications
2
24
1
Order By: Relevance
“…Likewise, the lack of contact with primary care physicians and pediatric subspecialty office closures may have increased acuity. In contrast, the relative proportional increase in acuity may in fact be due to a significant absolute decline among lower acuity patients [ 27 ], possibly resulting from an increase in self-management of non-emergent minor medical complaints at home.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, the lack of contact with primary care physicians and pediatric subspecialty office closures may have increased acuity. In contrast, the relative proportional increase in acuity may in fact be due to a significant absolute decline among lower acuity patients [ 27 ], possibly resulting from an increase in self-management of non-emergent minor medical complaints at home.…”
Section: Discussionmentioning
confidence: 99%
“…To date, most data reported has focused on PED trends before and during the pandemic peak [ 14 , 15 , 18 , 26 ] and a recent study looking beyond the height of the pandemic was limited to critically ill children [ 27 ]. Unique to our study, are the reported initial effects of a state phased re-opening on all PED trends in a known COVID-19 epicenter.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, pediatric EDs serve as regional referral centers providing specialized care, but data characterizing the clinical and financial impact of the COVID-19 pandemic on this practice setting is limited. [14][15][16] Finally, current studies do not explore whether the decline in ED visits differentially impacted certain pediatric conditions or whether resource utilization differed for patients seeking ED care during the pandemic. 14,15 As SARS-CoV-2 cases continue to rise among children, [4][5][6] an improved understanding of the clinical and financial impact of the COVID-19 pandemic specifically on pediatric ED care is needed.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] Finally, current studies do not explore whether the decline in ED visits differentially impacted certain pediatric conditions or whether resource utilization differed for patients seeking ED care during the pandemic. 14,15 As SARS-CoV-2 cases continue to rise among children, [4][5][6] an improved understanding of the clinical and financial impact of the COVID-19 pandemic specifically on pediatric ED care is needed. [14][15][16][17] Thus, we describe the epidemiology of pediatric ED visits and resource utilization at tertiary care children's hospitals in the US during the first five months of the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%